2014
DOI: 10.5511/plantbiotechnology.14.0917a
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids in plant rhizospheres: secretion, fate and their effects on biological communication

Abstract: Flavonoids, one of the most-described group of plant "specialized metabolites", consist of more than 10,000 structurally diverse compounds. Most flavonoids accumulate in plant vacuoles as glycosides, with some released by the roots into rhizospheres. These flavonoids are involved in biological communications with rhizobia, arbuscular mycorrhizal fungi, plant growth promoting rhizobacteria, pathogens, nematodes, and other plant species. Both aglycones and glycosides of flavonoids are found in root exudates and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 120 publications
(97 reference statements)
2
40
0
1
Order By: Relevance
“…There are two possible pathways for isoflavone secretion from roots, 12) with ICHG thought to be a key regulator of the secretion of malonylglucosides and glucosides 22,24 ) . Analysis of ICHG expression by real-time PCR showed that, during soybean development, ICHG expression was higher at vegetative stages, especially at V3 and V7, but was reduced during reproductive stages (Fig.…”
Section: Expression Of Ichgmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two possible pathways for isoflavone secretion from roots, 12) with ICHG thought to be a key regulator of the secretion of malonylglucosides and glucosides 22,24 ) . Analysis of ICHG expression by real-time PCR showed that, during soybean development, ICHG expression was higher at vegetative stages, especially at V3 and V7, but was reduced during reproductive stages (Fig.…”
Section: Expression Of Ichgmentioning
confidence: 99%
“…10) In addition to signaling rhizobia to induce the NodD gene, isoflavones play various roles in biological communications with soil microbes. 11,12) Although plants secrete a significant proportion of photosynthates into the rhizosphere from their roots, the mechanisms and genes involved in the root exudation are not fully understood. 13,14) Plant growth stages as well as the nutrient deficiency such as nitrogen, phosphate, and iron have been found to significantly affect the secretion of metabolites into the rhizosphere.…”
mentioning
confidence: 99%
“…Several forms of membrane transport have been proposed for flavonoids, including active secretion (Buer et al, 2007;Sugiyama et al, 2007;Cesco et al, 2010). Selective compound exudation hints that these chemicals perform a function for the tree, such as chemo-attractants, toxins, or inhibitors of particular microbial processes (Cesco et al, 2012;Sugiyama & Yazaki, 2014;Venturi & Keel, 2016). Through actively changing the secretion of root exudates, plants may also influence microbial respiration.…”
Section: Phenolic Release Into Soilmentioning
confidence: 99%
“…The greater abundance of nutrients near roots produces an environment in which microbes flourish and microbial abundance are greater in the rhizosphere than in bulk soils (Mendes, Garbeva, & Raaijmakers, ; Prashar, Kapoor, & Sachdeva, ). In contrast to primary metabolites, the stability of plant specialized metabolites varies depending on their chemical structure and biological activity (Sugiyama & Yazaki, ). For example, strigolactones are unstable in soil, making them a signal of living plant roots (Ruyter‐Spira, Al‐Babili, van der Krol, & Bouwmeester, ; Seto, Kameoka, Yamaguchi, & Kyozuka, ), whereas flavonoids are relatively stable in soil (Sugiyama, Yamazaki, Hamamoto, Takase, & Yazaki, ).…”
Section: Introductionmentioning
confidence: 99%
“…Largely due to the difficulty of analysing these metabolites in soil, most studies on plant specialized metabolites have been conducted in hydroponic culture or in sterile sand (Oburgera & Jones, ). However, root structure and metabolite fate differ in soil and under these artificial conditions (Crush, Care, Gourdin, & Woodfield, ; Sugiyama & Yazaki, ). To gain insight into the functions of plant specialized metabolites in field‐grown plants, it is important to analyse rhizosphere plant–microbe interactions using soils from crop fields.…”
Section: Introductionmentioning
confidence: 99%